Apolipoprotein E Induced Cognitive Dysfunction: Mediation Analysis of Lipids and Glucose Biomarkers in an Elderly Cohort Study - Liu, Linxin; Li, Huichu; Iyer, Hari; Liu, Andy J.; Zeng, Yi; Ji, John S. (Frontiers in Aging Neuroscience, 2021)
Introduction Prior evidence suggested Apolipoprotein E (APOE), lipids, and glucose metabolism may act through the same pathways on the pathogenesis of Alzheimer’s disease (AD). Methods This prospective study used data from the Chinese Longitudinal Healthy Longevity Study. We tested the associations of APOE genotype (ε2ε2, ε2ε3, ε2ε4, ε3ε3, ε3ε4, and ε4ε4) and cognitive function using generalized estimating equations (GEE). We examined for possible mediation and effect modification by lipids and glucose level in this association. Results APOE ε2 showed significant direct protective effect and indirect harmful effect through TC on cognitive function. Abnormal lipids or glucose levels were not consistently associated with cognitive dysfunction in our study. We did not detect significant indirect effects through lipids for APOE ε4 or any indirect effects through glucose. Discussion These findings suggested complicated relationships among APOE, lipids, glucose, and cognitive function. Further study can make validations in other populations.